The Condition of Postmodernity. An Enquiry into the Origins of Cultural Change (an excerpt) - Вфмшв Harvey (Journal of Economic Sociology, 2020)
The book by David Harvey, The Condition of Postmodernity. An Enquiry into the Origins of Cultural Change, presented deep research into the nature of postmodernism, considered not as a set of ideas but rather as historical conditions. The author claimed that roughly since 1972 cultural as well as political and economic practices changed globally, including the rise of postmodern cultural forms and the emergence of flexible capital accumulation. According to the author, those changes were conditioned by the new prevailing modes of how people experienced time and space, indicating the new cycle of time-space compression in the organization of capitalism. The book consists of four parts. In the first part, Prof. Harvey reviewed the dominating but conflicting theories of postmodernism. In the other chapters he considered the relationship between the dynamics of the historical and geographical development of capitalism, complicated processes of cultural production, and ideological transformation. The Journal of Economic Sociology publishes the tenth chapter, “Theorizing the Transition,” from the second part of the book, “The Political-Economic Transformation of Late Twentieth-Century Capitalism.” In this chapter, the author demonstrated that existing theories had difficulties in explaining the observed historical transition from Fordism to flexible accumulation. In order to overcome these problems, Harvey proposed a return to capitalism's origins to reconsider its logic generally with the help of Marx’s theories.